Regional Autonomy in Realizing Good Governance - Roy Marthen Moonti (Susbtantive Justice International Journal of Law, 2019)
Good Governance in regional autonomy is a phenomenon whose principle is talking about government or good government in terms of realizing good governance through the context of public services. The purpose of regional autonomy is solely to provide satisfaction to the community and prosperity of society in a government area. The purpose of this study is to determine the development of current regional autonomy in realizing Good Governance as intended. The research method used in the preparation of this study is a normative juridical method that is, in answering the problems of the realization of good governance, the legal point of view is based on the applicable legal regulations, henceforth it is connected with the reality in the field relating to the issues to be discussed. In terms of the development of regional autonomy, of course there are several things that are the main indicators, namely Equalization and Improvement of Development in the Regions, Improvement of Services for Communities, Optimization of Natural Resources and Human Resources in the Regions.